Knowledge, awareness, and perception on genetic testing for primary immunodeficiency disease among parents in Malaysia: a qualitative study - Ahmad Azahari, Ahmad Hazim Syakir; Hakim Zada, Farheen; Ismail, Intan Hakimah; Abd Hamid, Intan Juliana; Lim, Bruce Wee Diong; Ismail, Noor Akmal Shareela; Ali, Adli (Frontiers Media, 2024)
Background: Primary Immunodeficiency Disease (PID), also known as Inborn Errors of Immunity (IEI), comprises a group of rare genetic disorders that impair the body’s immune responses. These conditions result from monogenic germline mutations that affect the function of genes governing the innate and adaptive immune system. Therefore, individuals with PID are more susceptible to infectious diseases, allergies, and autoimmune and autoinflammatory conditions. The prevalence of PID has been on the rise, with the number of classified diseases reaching 404, and 430 genetic defects reported to cause these conditions. However, in Malaysia, genetic testing for PID is currently limited and needs to be outsourced to overseas laboratories, posing financial challenges for families. Moreover, limited research has focused on the knowledge and awareness of genetic testing among parents of children with PID in Malaysia. This study aims to address this gap and provide valuable insights into the knowledge, awareness, and perception of genetic testing among this specific population. Method: This qualitative cross-sectional study utilised online open-ended, semi-structured focus group interviews to explore the perceptions and experiences of parents of children with Primary Immunodeficiency (PID). Participants were recruited through convenience sampling from the Malaysian Patient Organisation for Primary Immunodeficiencies (MyPOPI), a non-governmental organisation dedicated to providing support and raising awareness about PID. The study spanned from May 2023 to July 2023 and included participants from diverse regions of Malaysia who had undergone different diagnostic journeys in various hospitals. Result: The focus group discussions yielded 11 sub-themes that highlighted the experiences, understanding and challenges of the participants regarding genetic testing based on the semi-structured questions. These sub-themes were then grouped into four main themes that are awareness and understanding of genetic testing, the journey towards diagnosis and treatment, emotional impact and psychological factors, and the importance of medical experts in diagnosing and managing PID, as well as public perception and awareness. Conclusion: In conclusion, this study highlights the diverse knowledge, awareness, and perception surrounding genetic testing for PID. Factors such as access to services, family history, and personal circumstances shape individuals’ understanding of genetic testing. The importance of healthcare professionals, along with the need for improved accessibility and targeted communication strategies, is underscored to enhance understanding and reduce stigma surrounding genetic testing for rare diseases like PID.